(untitled) (Journal of Medicine, 2008)
Background: The academic activities of the 1st and 2nd year MBBS students are running according to the new curriculum (Curriculum 2002). Curriculum is a series of planned activities to which the learner may be exposed in order to achieve the learning goals. But due to ongoing modifications of society, disease demography, medical science, concepts of teaching and availability of newer technique; curriculum may need to be changed. Assessment is the process of testing a student’s ability. A good assessment should be valid, reliable, practicable and objective. Without assessment the purpose of effective teaching will not fulfill. To change curricula, examination system or assessment system also needs to be changed. Though evaluation of students is an integral part of all educational processes, a suitable evaluation procedure is said to be lacking. So opinions of teachers as well as students are immensely important to develop an ideal evaluation procedure. Methodology: This cross-sectional prospective study was done in Dhaka Medical college over a period of 1 months.2nd year MBBS students( 100) and teachers of Physiology, Anatomy and Biochemistry (22) gave their opinion in this study in a mixed pattern of questionnaire ( both open-ended and closed) . Results: Majority of students( 84%) but minority of teachers opined that there was need of card completion examination as in course assessment system .Other teachers and students suggested for alternate examination instead of card completion examination like only MCQ (18%), both MCQ and SAQ (82%). Choice of venue of the examination were - tutorial class (58%), lecture class (21%), practical and tutorial class (21%). Discussion: Though present MBBS curriculum is a problem oriented scientific curriculum with modern concepts like MCQ, OSPE, SAQ and SOE; the teachers are facing a lot of problems in implementing the curriculum due to lack of orientation and shortage of manpower. Conclusion: In spite of criticisms Curriculum 2002 is a positive change in an academic field. In order to improve and update the curriculum; its planning should be constantly reviewed. Â DOI = 10.3329/jom.v8i2.1404 J MEDICINE 2007; 8 : 39-43